Intimate partner violence screening and response in New South Wales emergency departments: A multi‐site feasibility study. (21st January 2020) - Spangaro, Jo; Vajda, Jacqualine; Klineberg, Emily; Lin, Sen; Griffiths, Chris; Saberi, Elham; Field, Emma; Miller, Alex; McNamara, Lorna
Abstract: Objective: To test feasibility of a systematic approach to routine screening and response for intimate partner violence among women presenting to three New South Wales EDs. Methods: This prospective feasibility study was conducted over 6 months in two rural and one major tertiary metropolitan ED in New South Wales. Women aged 16–45 years triaged category 3–5 (treat within 30 min/1 h/2 h), who could be approached privately, were screened for intimate partner violence using the validated HITS (Hurts, Insults, Threatens and Screams or Swears) tool. The follow‐up protocol for patients who disclosed abuse, specified a social work/psychology (psychosocial) response within 1 h. Outcomes of interest were screening rates of eligible presentations, disclosures of abuse, psycho‐social referral and responses. Interviews conducted with ED medical directors and nurse unit managers at each site explored barriers and facilitators. Results: A total of 1047 women (11.4% of eligible presentations) completed screening at their first or subsequent presentation. Of 868 women screened on first presentation, 18% ( n = 154) disclosed intimate partner violence, with no significant differences by age group, country of birth, triage category or time/day of arrival. Key barriers to screening were high patient volume, absence of electronic prompts and lack of privacy. Of those who screened positive 49% ( n = 75) received an immediate, on‐site psycho‐social response. Conclusion: The present study demonstrates that it is both possible and relevant, given the 18% disclosure rate, to screen women in relation intimate partner violence in EDs and provide a psycho‐social response within 1 h. More needs to be done to address barriers to screening to provide opportunities for early intervention.